Dissection of the microRNA Network Regulating Hedgehog Signaling in Drosophila - He, Tao; Fan, Yu; Wang, Yao; Liu, Min; Zhu, Alan Jian (Frontiers in Cell and Developmental Biology, 2022)
The evolutionarily conserved Hedgehog (Hh) signaling plays a critical role in embryogenesis and adult tissue homeostasis. Aberrant Hh signaling often leads to various forms of developmental anomalies and cancer. Since altered microRNA (miRNA) expression is associated with developmental defects and tumorigenesis, it is not surprising that several miRNAs have been found to regulate Hh signaling. However, these miRNAs are mainly identified through small-scale in vivo screening or in vitro assays. As miRNAs preferentially reduce target gene expression via the 3’ untranslated region, we analyzed the effect of reduced expression of core components of the Hh signaling cascade on downstream signaling activity, and generated a transgenic Drosophila toolbox of in vivo miRNA sensors for core components of Hh signaling, including hh, patched (ptc), smoothened (smo), costal 2 (cos2), fused (fu), Suppressor of fused (Su(fu)), and cubitus interruptus (ci). With these tools in hand, we performed a genome-wide in vivo miRNA overexpression screen in the developing Drosophila wing imaginal disc. Of the twelve miRNAs identified, seven were not previously reported in the in vivo Hh regulatory network. Moreover, these miRNAs may act as general regulators of Hh signaling, as their overexpression disrupts Hh signaling-mediated cyst stem cell maintenance during spermatogenesis. To identify direct targets of these newly discovered miRNAs, we used the miRNA sensor toolbox to show that miR-10 and miR-958 directly target fu and smo, respectively, while the other five miRNAs act through yet-to-be-identified targets other than the seven core components of Hh signaling described above. Importantly, through loss-of-function analysis, we found that endogenous miR-10 and miR-958 target fu and smo, respectively, whereas deletion of the other five miRNAs leads to altered expression of Hh signaling components, suggesting that these seven newly discovered miRNAs regulate Hh signaling in vivo. Given the powerful effects of these miRNAs on Hh signaling, we believe that identifying their bona fide targets of the other five miRNAs will help reveal important new players in the Hh regulatory network.